Sodium Citrate Versus Heparin Locking Solutions for Tunneled Hemodialysis Catheters - Patrícia Alves; Rita Veríssimo; Artur Mendes (Publicações Ciência e Vida, 2023)
Introduction: Hemodialysis catheter dysfunction compromises dialysis adequacy and may limit catheter survival. Strategies to prevent hemodialysis catheter dysfunction include catheter locks, generally either with heparin or citrate. Methods: Our hemodialysis unit converted to locking all central venous hemodialysis catheters with sodium citrate 4% instead of heparin 5000 U/mL. A retrospective analysis compared the outcomes of the 6 months prior and after the conversion. The compared outcomes were incidence of catheter thrombosis, catheter-related infection, flow-related catheter exchange rate, dialysis efficiency measured by Kt/V and catheter dysfunction. Results: Twenty-three patients were included. Between the two audit periods, the rate of catheter thrombosis was 0 (0 per 1000 catheter days) and 7 (2.78 per 1000 catheter days) during the heparin and citrate period respectively (p=0.109). The number of catheter exchanges due to catheter dysfunction was 0 (0 per 1000 catheter days) during the heparin period and just 1 (0.39 per 1000 catheter days) during the citrate period (p=0.317). Dialysis adequacy measured by KT/V was 1.54 (0.39) in the heparin group and 1.54 (0.35) in the citrate group (p=0.465). Catheter dysfunction was recorded in 146 sessions (12.3%) in the heparin period and in 159 sessions (14,7%) in the citrate period (p=0.234). There were no catheter related infections in either group. Conclusion: There was a 58% cost reduction associated with catheter-locking therapy between the heparin period and the citrate period. This cost reduction included the costs associated with alteplase use. Besides the financial advantages in switching to citrate locking, there are other potential advantages, namely the minimization of heparin related side effects or limitations.